Comparing the genetic changes detected in the primary and secondary tumor sites of ovarian cancer using comparative genomic hybridization. Issue 2 (1st February 2005) - Fishman, A.; Shalom-Paz, E.; Fejgin, M.; Gaber, E.; Altaras, M.; Amiel, A.
Abstract : Our objective was to compare the genetic abnormalities in the primary tumors of epithelial ovarian cancer and their associated secondary peritoneal implants using comparative genomic hybridization (CGH). CGH was performed on seven apparent stage III ovarian serous cancer cases. Dissected tissue samples from the primary tumor and from the metastatic peritoneal implant were obtained at initial surgical staging and analyzed in each case. We used CGH as this technique allows the entire genome of the tumor to be examined simultaneously for chromosomal imbalances without the need for tissue culture or targeting of specific loci. The chromosomal abnormalities detected in the distinct sites were then reviewed and compared. CGH studies were successful in all 14 samples from the seven patients. The analysis revealed chromosomal aberrations in six patients with certain repeated changes as amplification of 1q, 2p, 2q, 3q, 6q, 8q, and 12p and underrepresentation of 18q and X chromosomes. Comparing the genomes of the primary tumors with the metastatic samples showed four cases with a balanced metastatic CGH profile while the primary site was aberrant. Greater chromosomal complexity associated with the primary site was detected in two other patients. In one case, both primary and secondary sites had no detectable chromosomal imbalances. The cytogenetic patterns in six of the seven primary tumors showed complex karyotypic changes, unlike the inconsistent findings that were associated with the secondary sites. The chromosomes of the secondary sites expressed either normal genomes or fewer genetic aberrations. Such genomic heterogeneity between the primary and secondary sites may indicate that the secondary peritoneal implants are de novo carcinogenesis occurrences. The results may support the concept that at least part of advanced ovarian cancer is a multicentric disease in the early stages. Further genetic studies are needed to reassess this assumption.